Beyond 50. challenges at work for older nurses and allied health workers in rural Australia: a thematic analysis of focus group discussions - Depczynski Julie C; Fragar Lyn J (BMC, 2011)
Abstract Background The health workforce in Australia is ageing, particularly in rural areas, where this change will have the most immediate implications for health care delivery and workforce needs. In rural areas, the sustainability of health services will be dependent upon nurses and allied health workers being willing to work beyond middle age, yet the particular challenges for older health workers in rural Australia are not well known. The purpose of this research was to identify aspects of work that have become more difficult for rural health workers as they have become older; and the age-related changes and exacerbating factors that contribute to these difficulties. Findings will support efforts to make workplaces more 'user-friendly' for older health workers. Methods Nurses and allied health workers aged 50 years and over were invited to attend one of six local workshops held in the Hunter New England region of NSW, Australia. This qualitative action research project used a focus group methodology and thematic content analysis to identify and interpret issues arising from workshop discussions. Results Eighty older health workers from a range of disciplines attended the workshops. Tasks and aspects of work that have become more difficult for older health workers in hospital settings, include reading labels and administering medications; hearing patients and colleagues; manual handling; particular movements and postures; shift work; delivery of babies; patient exercises and suturing. In community settings, difficulties relate to vehicle use and home visiting. Significant issues across settings include ongoing education, work with computers and general fatigue. Wider personal challenges include coping with change, balancing work-life commitments, dealing with attachments and meeting goals and expectations. Work and age-related factors that exacerbate difficulties include vision and hearing deficits, increasing tiredness, more complex professional roles and a sense of not being valued in the context of greater perceived workload. Conclusions Older health workers are managing a range of issues, on top of the general challenges of rural practice. Personal health, wellbeing and other realms of life appear to take on increasing importance for older health workers when faced with increasing difficulties at work. Solutions need to address difficulties at personal, workplace and system wide levels.